The discourse of power and knowledge in the social sciences and study of Muslim society - Mohd. Yusof, Danial (Taylor & Francis, 2012)
This article examines parallels between contemporary Western and Muslim thought. It proposes that there is congruence in Western and Muslim political thought on issues of soft foundationalism, negative theology, provisional truth claims and religious democracy to offset hegemonic tendencies. In the social sciences, specifically political science, the neutralization of ideology is also supported in response to concern about ideological encroachments into the discipline. In addition, the article discusses the residual issue of positivism and knowledge as social construction, i.e. the social sciences themselves as ideological with regard to the agnostic position of their methodology. This has implications for the study of religion, in this case Islam, and the field's problematic nomenclature, such as Islamism and, now, post-Islamism. This is explored through a discussion of the Arab Spring and Malaysian politics. The article concludes that similar concerns on the relationship between power and knowledge in contemporary Western and Muslim thought are beneficial to the social sciences and their study of the Muslim world's transformation as a social and political phenomenon.